Pasantía de diseño y aprobación de proyectos con la empresa Kubo Arquitectos, Málaga, España (2020)
During the 6 months of the practice I participated in the development of 13 projects mainly in the calculation of installations, measurements, budgets and documentation of start and end of work. The internship in Malaga contributed to my personal growth in terms of having greater autonomy, responsibility, time management, discipline, learning to relate to people from another culture and in opportunities with the use of a second language. As for the contributions to professional life, I had the opportunity to participate in the development of architectural projects, to learn to make budgets, administrative steps to obtain building licenses, I also had the opportunity to get to know different European cities in which I could observe and be immersed in different types of urban organization that have mixtures of architectural styles such as the Mudejar, Gothic, classical, Roman and avant-garde among others depending on the time of its construction and the evolution of the city.